Ionic liquid matrices for improved detection of proteins and polymers in time‐of‐flight secondary ion mass spectrometry. (7th July 2014) - Dertinger, Jennifer J.; Walker, Amy V.; Lee, Yeonhee; Moon, DaeWon; Kang, Hee Jae; Kim, Kyung Joong; Lee, Tae Geol; Lee, Jae Cheol; Yi, Keewook; Hong, Tae Eun
<x xml:space="preserve">Abstract</x> The analyte signal enhancements of polymers and proteins were investigated using ionic liquid (IL) matrix‐enhanced SIMS. The molecular weight of the polymer does not play a significant role in determining the magnitude of the n‐mer and oligomer ion intensity enhancements. The analyte ion intensities enhancements are strongly dependent on the chemistry of the polymer side and terminal groups. Further, it was observed that ILs based on the matrix‐assisted laser desorption/ionization matrix 2, 5 dihydroxybenzoic acid were the most effective matrices. The molecular ion intensity enhancements of peptides including bradykinin were also investigated. Using bradykinins with different terminal amino acids, it is observed that molecular ion intensities are significantly enhanced using IL matrices if the N or C terminal amino acid can accept (or donate) a proton. Copyright © 2014 John Wiley & Sons, Ltd.